Psychological Stresses among Divorced Professional Women - Mohamed Sharif, Mustaffa; Chan Hsin Chlen, Samuel; Amalia, Madihie; Jamayah, Saili; Aqeel, Khan (2017)
The study explored the psychological stresses due to divorce among professional women. The purpose of this study was to examine the relationship of factors, impacts and coping mechanisms in divorce in relation to psychological stress among professional women. This research utilized the mixed method approach with sequential exploratory strategy. The quantitative data from Revised Perceived Stress Scale (PSS)-10 were administered to support the qualitative findings. This data gave an initial feature on psychological stress among divorced professional women. In this study, eighteen respondents participated by employing purposive sampling. The data gathered from the Malaysian stratified probability sample in which the divorce was indicated among respondents. The common background of all respondents were they worked at university or college. This study discovered that occupational prestige and stubbornness are two main psychological stresses which have affected their marriage. This study has produced a framework to raise awareness of forgiveness and skill of adjustment that enabled a divorced professional woman to seek emotional stability. It was proposed that this framework was used for a more thorough research on culture and social norms on a domestic level. For future research, it is recommended that a more in-depth qualitative method focusing on stress level in divorced among professional women were utilized for further studies. To conclude, a gap has identified and existed in life experiences among the professional women in developing countries.